2016
DOI: 10.3390/en9080660
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Burden of Food Waste: The Double Energy Waste in Italy

Abstract: Abstract:The energy intensity of modern food systems represents a major issue in a scenario of decreasing oil resources and increasing population. Beside the use of renewable energy, an increased efficiency in food systems could contribute to reduce fossil fuels dependence. In this sense, food losses and waste (FLW) have crucial consequences on the energy balance. Based on the concept of "embodied energy", food wastage can be framed as a double waste of energy, both in terms of non-consumed food energy and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…The results of the energy flow analysis determined a total EEL value of 17% in relation to the total PED along the entire supply chain, showing the consumption stage as the most inefficient one. This is in accordance with Vittuari et al [7], who assume that embodied energy builds up along the chain, so the latter the FL occurs, the greater the energy loss. The EEL results indicate that in the final part of the food supply chain, which means the sum of the distribution stage plus the consumption stage, the highest amount of EEL is concentrated.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of the energy flow analysis determined a total EEL value of 17% in relation to the total PED along the entire supply chain, showing the consumption stage as the most inefficient one. This is in accordance with Vittuari et al [7], who assume that embodied energy builds up along the chain, so the latter the FL occurs, the greater the energy loss. The EEL results indicate that in the final part of the food supply chain, which means the sum of the distribution stage plus the consumption stage, the highest amount of EEL is concentrated.…”
Section: Discussionsupporting
confidence: 91%
“…However, this is not a new phenomenon; in fact, in the energy crisis of the 70s, Pimentel et al [3] found that the energy efficiency of modern food production was declining. Over time, the energy inputs began to be higher than the energy outputs [4], and according to Cuellar and Webber [5], Lin et al [6] and Vittuari et al [7], nowadays the food supply chain requires 10-15 kJ of fossil fuel to produce 1 kJ of food. From the whole supply chain, the high-energy intensity of agriculture has meant an enormous increase in the consumption of fossil fuels; however, this is common in all phases of the food supply chain and it varies depending on the type of product and processing level.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although food loss and food waste occurs throughout the whole food supply chain, from farm to table, food waste at the consumer stage attracts particular attention because the relatively large amount of consumer food waste means that all resources input at production, processing, storage, and distribution stages was used in vain, and a significant amount of greenhouse gas (GHG) emissions occurring at these stages and at waste management is added [5]. Besides, considering the rapid growth of the global population and the declining of the per capita availability of resources and energy for food production, food waste also intensifies the global food shortage and malnourishment [6].…”
Section: Introductionmentioning
confidence: 99%